2014
DOI: 10.1002/14651858.cd009728.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention for improving school achievement in overweight or obese children and adolescents

Abstract: , J. (2014). Lifestyle intervention for improving school achievement in overweight or obese children and adolescents. Cochrane database of systematic reviews, 3, CD009728.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 102 publications
1
42
1
2
Order By: Relevance
“…Waters et al (20) así como Mancipe Navarrete et al (21) mencionan en sus respectivas revisiones sistemáticas, que las intervenciones orientadas a la prevención de la obesidad que sean llevadas a cabo en los colegios deben incluir componentes de alimentación saludable, actividad física e imagen corporal, todas estas estrategias deben tener una correcta adaptación cultural que ayude a la adherencia no solo de los niños sino de su familia y entorno cercano. De forma similar, Martin et al (22) enfatizan la importancia de que la medición de la efectividad de estas estrategias debe ser medida no solo desde el punto de vista de la actividad física, sino también de efectos psicológicos y conductuales. En el caso del programa "Desde niños, juntos contra la diabetes", una de las principales limitaciones que se tuvo es la no medición del efecto en el estado nutricional o la evaluación antropométrica; por lo que futuros estudios que deseen usar este programa modelo, deben orientar sus conclusiones hacia ello.…”
Section: Discussionunclassified
“…Waters et al (20) así como Mancipe Navarrete et al (21) mencionan en sus respectivas revisiones sistemáticas, que las intervenciones orientadas a la prevención de la obesidad que sean llevadas a cabo en los colegios deben incluir componentes de alimentación saludable, actividad física e imagen corporal, todas estas estrategias deben tener una correcta adaptación cultural que ayude a la adherencia no solo de los niños sino de su familia y entorno cercano. De forma similar, Martin et al (22) enfatizan la importancia de que la medición de la efectividad de estas estrategias debe ser medida no solo desde el punto de vista de la actividad física, sino también de efectos psicológicos y conductuales. En el caso del programa "Desde niños, juntos contra la diabetes", una de las principales limitaciones que se tuvo es la no medición del efecto en el estado nutricional o la evaluación antropométrica; por lo que futuros estudios que deseen usar este programa modelo, deben orientar sus conclusiones hacia ello.…”
Section: Discussionunclassified
“…This transition is characterized by rapid, interrelated changes in body, mind, and social relationships [4]. Most discussions concerning adolescent health promotion include the topic of improved bio-psychosocial wellbeing, for example, by enhancing regular exercise, nutrition, stress management, spiritual life, and interpersonal relationship behaviors [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Research concerning adolescent health promotion issues has increased markedly since the 1980s and has been extended to include individual, family, and community contexts [6]. Such studies have shown that the prevalence of metabolic syndrome is high among adolescents who are inactive and adopt an inadequate diet; further, many countries report low levels of cardio-respiratory fitness in adolescents [811].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prevalence rates in many industrialized countries around the world have started stabilizing since 2004 (1), they still remain at a high level. Due to the direct and indirect implications of childhood obesity, effective treatment and prevention interventions are of utmost importance (2). During the last 3 decades, a number of empirical and theoretical works have focused on the development of obesity in children.…”
mentioning
confidence: 99%